Receptive vocabulary knowledge tests: Their potential importance for planning a well-balanced vocabulary component of a language program - Wakeling, Elliott (2015)
iii Abstract Nation and Webb (2011) state ‘Testing is one of the major jobs of the vocabulary teacher, because without good information about our learners’ vocabulary knowledge, we cannot do the most important job of planning a well-balanced program’ (p. 219). This paper evaluated different receptive vocabulary knowledge tests and assessed their potential to help a teacher plan a well-balanced vocabulary program. The Vocabulary Levels Test (VLT) was selected to assess the vocabulary knowledge of grade seven and eight students. Also, questionnaires were used to ask the students about their English learning background and the vocabulary learning strategies they use to develop their vocabulary knowledge. The findings show the VLT can help language teachers plan a well-balanced vocabulary program because it reliably identifies what level of vocabulary knowledge a student needs to focus on during a language course. The results of the vocabulary learning strategies questionnaire indicate many of the recommended strategies are not regularly used by students, and these findings indicate there is scope to promote these strategies within a vocabulary program. The VLT is a useful diagnostic test for planning and placement purposes, but additional vocabulary assessments and a vocabulary learning framework are needed to refine a vocabulary component of a language program. In addition, further practitioner research is needed to evaluate the effectiveness of pedagogical decisions that are based on the VLT results.